2009
DOI: 10.1107/s1600536809031900
|View full text |Cite
|
Sign up to set email alerts
|

(Z)-3-(9-Anthryl)-1-(2-thienyl)prop-2-en-1-one

Abstract: There are two crystallographically independent mol­ecules in the asymmetric unit of the title heteroaryl chalcone, C21H14OS: the dihedral angle between the thio­phene and anthracene rings is 75.07 (17)° in one mol­ecule and 76.32 (17)° in the other. The crystal structure is consolidated by short C⋯O [3.348 (5)–3.394 (5) Å], C⋯S [3.607 (5)–3.666 (5) Å] and S⋯O [2.926 (3) Å] contacts, as well as by C—H⋯π and π–π inter­actions [Cg⋯Cg = 3.745 (3) Å].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…The bond distances (Allen et al, 1987) and angles are normal and comparable to those found in closely related structures (Fun et al, 2009;Suwunwong et al, 2009).…”
Section: Methodssupporting
confidence: 77%
See 2 more Smart Citations
“…The bond distances (Allen et al, 1987) and angles are normal and comparable to those found in closely related structures (Fun et al, 2009;Suwunwong et al, 2009).…”
Section: Methodssupporting
confidence: 77%
“…Chalcones have been studied for their wide range of applications such as non-linear optical (Patil & Dharmaprakash, 2008) and fluorescent properties (Svetlichny et al, 2007) and biological activities (Saydam et al, 2003). We have previously reported crystal structures of chalcone derivatives containing the anthracene moiety which exist in both the E (Suwunwong et al, 2009) and Z configurations (Fun et al, 2009). The title compound was synthesized to study its fluorescent properties in addition to its antibacterial activity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a related structure and background references to chalcones, see: Fun et al (2010). For related structures, see: Chantrapromma et al (2009Chantrapromma et al ( , 2010; Fun et al (2009); Horkaew et al (2010); Lu et al (2009); ; Wang et al (2009Wang et al ( , 2010; Jasinski et al (2011). For hydrogen-bond motifs, see: Bernstein et al (1995).…”
Section: Related Literaturementioning
confidence: 99%
“…In continuation of our studies on the crystal structures of chalcones (Fun et al, 2010), we now report the synthesis and crystal structure of the title compound, (I). The structures of some related chalcones viz: (Z)-3-(9-anthryl)-1-(4-methoxyphenyl)prop-2-en-1-one (Chantrapromma et al, 2009), (Z)-3-(9-anthryl)-1-(2-thienyl)prop-2-en-1-one (Fun et al, 2009), (E)-3-(anthracen-9-yl)-1-(4-bromophenyl)prop-2-en-1-one , (Z)-3-(9-anthryl)-1-(4-bromophenyl)-2-(4-nitro-1H-imidazol-1-yl)prop-2-en-1-one (Lu et al, 2009) (Horkaew et al, 2010), and an orthorhombic polymorph of (Z)-3-(9-anthryl)-1-(2-thienyl)prop-2-en-1-one (Chantrapromma et al, 2010) and 2(E)-3-(4hydroxyphenyl)-1-(4-chlorophenyl) prop-2-en-1-one (Jasinski et al,2011) have been reported.…”
Section: S1 Commentmentioning
confidence: 99%